Mathematical Modeling of Temperature Fields in Cultivation Structures - Biliaieva, V. V.; Shcherbyna, S. A. (Science and Transport Progress, 2024)
Purpose. The main purpose of the article is to develop a method for calculating thermal fields in greenhouse soil in the case of its artificial heating. Since the temperature regime in greenhouse soil has a significant impact on plant yields, it is very important, on the one hand, to ensure the required temperature in the soil, and on the other hand, to determine the energy-saving heating regime. Methodology. The method is based on the numerical integration of the heat transfer equation. A two-dimensional heat transfer equation was used to analyze and predict the unsteady process of soil heating in a greenhouse under artificial heating, and two finite-difference schemes were used to solve it. On the basis of the constructed numerical models, a computer program was developed to conduct a computational experiment. Findings. Effective computer models have been created to predict the unsteady formation of thermal zones in the greenhouse soil during its artificial heating. The results of numerical modeling are presented. Originality. Prognostic numerical models have been developed to analyze the dynamics of thermal fields formation in greenhouse soil during its artificial heating. On the basis of the developed numerical models, a set of application programs was created to conduct a computational experiment to determine the unsteady temperature field in greenhouse soil. The constructed numerical models belong to the class of «operational models», i.e., they are designed for the operational analysis of thermal fields in the soil. For the practical use of the developed numerical models, standard input information is required. Practical value. The constructed numerical models are a tool for analyzing the dynamics of soil heating and can be used in the development of energy-saving heating technology. These models can be used to determine the time of optimal soil heating in different zones (root system, soil surface) and to determine the rational location of heating elements, the time when the heating elements should be turned off, and the time when they should be turned on again. These models allow us to develop an energy-saving technology for heating the soil in a greenhouse.